2000
DOI: 10.1164/ajrccm.161.5.9906076
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Bronchiolitis in Infancy Is an Important Risk Factor for Asthma and Allergy at Age 7

Abstract: We previously reported an increased risk for bronchial obstructive disease and allergic sensitization up to age 3 in 47 children hospitalized with a respiratory syncytial virus (RSV) bronchiolitis in infancy compared with 93 matched control subjects recruited during infancy. The aims of the present study were to evaluate the occurrences of bronchial obstructive disease and allergic sensitization in these children at age 7(1)/ (2). All 140 children reported for the follow-up, which included physical examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
754
8
32

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 982 publications
(822 citation statements)
references
References 34 publications
28
754
8
32
Order By: Relevance
“…Furthermore, infants with a history of early hospitalized RSV-confirmed bronchiolitis were more prone to at least one wheezing episode than those with no such history (47% vs. 15·5%), irrespective of their prematurity status, during the CASTOR follow-up period. Our results are consistent with previously published data [38,39], but with lower incidences than those found by Sigurs et al in 3-year-old children with RSV bronchiolitis during the first year of life (60% of infants with RSV history with any wheezing episodes vs. 32% of those with no history, P = 0·003) [12]; those authors confirmed the same tendency in this birth cohort up to the age of 7 years [13]. The ALSPAC Study Team showed a lower prevalence of any wheezing (28%) at 30-42 months after birth in the RSV subgroup (150 infants) of this large British birth cohort compared to our results (47%), despite a very close prevalence in controls (13% and 15·5%, respectively).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, infants with a history of early hospitalized RSV-confirmed bronchiolitis were more prone to at least one wheezing episode than those with no such history (47% vs. 15·5%), irrespective of their prematurity status, during the CASTOR follow-up period. Our results are consistent with previously published data [38,39], but with lower incidences than those found by Sigurs et al in 3-year-old children with RSV bronchiolitis during the first year of life (60% of infants with RSV history with any wheezing episodes vs. 32% of those with no history, P = 0·003) [12]; those authors confirmed the same tendency in this birth cohort up to the age of 7 years [13]. The ALSPAC Study Team showed a lower prevalence of any wheezing (28%) at 30-42 months after birth in the RSV subgroup (150 infants) of this large British birth cohort compared to our results (47%), despite a very close prevalence in controls (13% and 15·5%, respectively).…”
Section: Discussionsupporting
confidence: 93%
“…In the Tucson Children's Respiratory Study, early RSV LRTI was an independent risk factor of subsequent wheezing up to age 11 years but ceased to be so at age 13 years [11]. Sigurs and colleagues demonstrated an increased prevalence of asthma or recurrent wheezing and allergic sensitization in a cohort of infants hospitalized with RSV bronchiolitis during the first year of life compared to a matched control cohort at ages 3, 7 and 13 years [12][13][14]. Recently, the same group showed that severe RSV bronchiolitis, requiring hospitalization during the first year of life, is frequently followed by allergic asthma persisting into early adulthood [15], contrasting with previous data suggesting a shorter post-RSV bronchial hyperresponsiveness [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…20,21 This is in line with the evidences that the epithelial barrier in young asthmatics is inherently abnormal 22 and that RSV bronchiolitis is a more important risk factor for the development of asthma and atopy up to the age of 7 years than heredity or environmental factors. 23 Moreover, the candidate genes showing significant association with both the phenotypes, when the case groups were compared with adult controls separately (childhood asthma vs adult control and adult asthma vs adult control), were the same as those observed in the combined analysis (all asthma vs all controls). Thus, TNF, ADAM33 and NOS1 might represent the common susceptibility gene for adult and childhood asthma.…”
Section: Discussionmentioning
confidence: 73%
“…14% to 40% of bronchiolitis patients will eventually have asthma [25,196], with the association persisting into adulthood [196][197][198][199][200][201][202][203]. In young children, asthma is heralded by acute bronchiolitis in 90% of cases, one third of which require hospitalization [204].…”
Section: Predicting Whether a Bronchiolitis Patient Will Later Be Diamentioning
confidence: 99%